(untitled) - Tonguthai, Kamonporn (Bangkok, 1985)
This paper has been produced as a background paper for those interested in fish diseases ans especially for those concerned about the disease outbreak which is currently taking place in Thailand and those who are attempting to identify its cause
Keywords: Aquatic animal diseases